#TITLE_ALTERNATIVE# - (NIM: 23708001); Pembimbing : Dr. Ir. Aditianto Ramelan, SUGIANTO
Nickel electroplating is one of the finishing processes in order to improve metal surface in aspect on engineering of decorative or engineering. One of application of nickel plating in manufacturing process is used to protect the mould cavities in plastic injection process and continuous caster in steel production. Aluminum can not be directly plated with nickel due to passivity of aluminum oxide on its surface. Immersing in basic zincate (ZnO and NaOH) solution will remove the oxide film and replace it with zinc film. The bonding strength of kel film on specimen is influenced by the immersion time and ZnO concentration. This researched is carried out to observe the mechanical i.e. hardness, its bonding strength and its appearance. The information obtained will be used for making a consideration of applying nickel coating on aluminum for pewter mould making. The ZnO concentration and nickel electroplating parameters were varied to find the optimum result. It is found that immersing the specimen for 10 second in 80 g/l ZnO and 400 g/l NaOH has resulted the best bonding strength in comparison with the 40 g/l and 60 g/l ZnO with the same NaOH concentration. The maximum bonding strength obtained from peel test is 13.8 N/mm per its width. The optimum conditions i.e. current density 30 A/dm2, pH 4, temperature 50OC and 20 minutes of plating time were found by varying electroplating parameters in citrate bath. The average maximum hardness of the nickel film together with best appearance is 178+22 VHN. From the observation it is concluded that the result obtained is still too low to be able to be used as a pewter mould inner coating hence further research should be carried out further.